Joyce in Pula, James Joyce Studies, 21.06.- 02.07.2004. IUC Dubrovnik, Hrvatska - Gjurgjan, Ljiljana Ina (2004)
The lecture is a homage to Ivo Vidan's research on Joyce's impact on the Pula's self-imagining. It also addresses the more recent research on the complexities of the national and cultural life in Austro-Hungarian Pula at the time when Joyce lived there and so might have been acquainted with them.